How much does using the Mind Mapping learning approach "improve" the grasp of mathematical ideas in junior high school students? - Jayanti, Eka Fitria; Choirudin, Choirudin; Anwar, M. Saidun; Manivannan, Rathish; Saputra, Jefry Angga (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
The learning model is a teacher's tool in the form of structured images that are presented to students. The learning model applied aims to improve students' understanding of mathematical concepts. The author determines the purpose of this study. Namely to assess the impact of experiments on the subject's knowledge of mathematical concepts in geometry material. This type of research uses experimental research using a mind mapping learning model with a pre-experimental design, one-group pretest-posttest. Tests were carried out randomly or through cluster sampling on building materials class VII Realschule. The data collection tool that the researchers used for this research was a test designed to test students' understanding of concepts. The researcher interviewed teachers, students, and documents in this data collection method. A hypothesis test was carried out on the data obtained after conducting a sig5% level t-test, normality test, and homogeneity test on statistical data. It was found that students could not understand mathematical concepts (mind mapping). This dramatically influences the results of understanding mathematical concepts. After using this method, students receive higher performance scores than before. Based on the t-test results, we can conclude the difference in the value of learning outcomes before and after applying the author's teaching method.